Webinar Series on Graduate On Time (GoT) - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2021)
The Institute of Graduate Studies has successfully organised two (2) webinar series on “Graduate on Time” (GoT), entitled: “10 Proven Ways to GoT: Tips from Successful PhD Graduates” and “Gateway to GoT: 10 Little Known Strategies from the Most Successful Supervisors”. These webinar series serve the purpose of promoting the awareness among students and supervisors regarding the importance of Graduates on Time (GOT) and taking on the responsibility in materialising the government’s goal for an increased percentage of students that successfully GOT. By carrying out these webinar series, it is hoped that students and supervisors alike will be able to acquire invaluable and fresh insights, strategies, and tips from guest speakers in aiding the postgraduate students to GOT.